Thyroid hormone concentrations associated with age, sex, reproductive status and apparent reproductive failure in the Amazon river dolphin (Inia geoffrensis). Issue 1 (1st August 2019) - Robeck, T R; Amaral, R S; da Silva, V M F; Martin, A R; Montano, G A; Brown, J L
Abstract : Thyroid hormones play important roles in metabolic and reproductive function; however, they have not been described in detail for any river dolphin species. We characterize these hormones across different age, sex and pregnancy status in the Amazon river dolphin in order to provide baseline normal values for this increasingly threatened species. Abstract: This study was conducted to characterize immunoreactive thyroid hormone concentrations in wild Amazon river dolphins, also called boto ( Inia geoffrensis ) by age group, sex, pregnancy and lactation status, and to determine if thyroid hormone concentration differences could be detected between pregnant females with and without successful parturition outcomes. Radioimmunoassays were used to analyse total T 3 and total T 4 in 182 serum samples collected from 172 botos living in the Mamirauá Sustainable Development Reserve, in the Brazilian Amazon from 2003 through 2015. Age significantly affected t T 3 and t T 4 concentrations in males, with values in immature males and females being significantly lower than those in adult males, whereas no age effects were noted between immature females and adult non-pregnant, non-lactating females. Significant sex differences were noted in t T 3 concentrations between immature males and females and in t T 4 concentrations between adult males and females. These resulted in significant differences in the t T 3 :t T 4 ratio between males and females within the immature and adult groups. Lactating and non-pregnant adult females had significantly higher t T 3 concentrations than pregnant females, and this difference was primarily driven by a 12% drop in t T 3 concentrations during the last two-thirds of pregnancy. No differences in thyroid hormone concentrations were detected between females diagnosed as pregnant and later found to have or not have a live calf. These results are the first to define thyroid hormone reference intervals and normal physiological variations in a wild population of river dolphins.